The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/app.10751
|View full text |Cite
|
Sign up to set email alerts
|

Formation and investigation of epoxy intumescent compositions modified by active additives

Abstract: ABSTRACT:Results are reported of research on intumescent composites based on epoxy resin cross-linked with polyethylene polyamine and containing ammonium polyphosphate and such modifying additives as calcium borate, manganese dioxide, nickel, and chromium, containing tubulenes as gas-formers and carbonization stimulators. The changes in composition and physicochemical properties of modified compositions under conditions of heat and fire were investigated by X-ray photo-electron spectroscopy, atomic force micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…The relocation rate of heat through the charring layers depends on the expansion and structure of the residual char. The expansion and structure of the char are very vital to common fire‐retardant properties of coatings 13…”
Section: Resultsmentioning
confidence: 99%
“…The relocation rate of heat through the charring layers depends on the expansion and structure of the residual char. The expansion and structure of the char are very vital to common fire‐retardant properties of coatings 13…”
Section: Resultsmentioning
confidence: 99%
“…Kodolov et al 83 reported a study on intumescent composites based on epoxy resins crosslinked with polyethylene–polyamine and containing APP and such co‐additives as calcium borate, manganese dioxide and nickel‐ or chromium‐containing tubulenes (products of dehydration and polycondensation of phenanthrene containing Ni or Cr) as carbonization stimulators. In fact, the introduction of metal‐containing tubulenes led to compositions with low flammability and high char yield, whereas the use of calcium borate considerably increased the strength of the intumescent foam being formed.…”
Section: Flame‐retardant Epoxiesmentioning
confidence: 99%
“…The gap between the HV and ground electrodes is defined as 50 mm. All specimens were tested in a closed cabinet with an open roof and minimum air circulation (Kodolov et al, 2002). …”
Section: Literature Review and Hypothesesmentioning
confidence: 99%